A Bibliometric Review on Esports Participation: View from Malaysia - Lim, Chee Ngee; Goh, Yen Nee; Mohd Isa, Salmi; Thurasamy, Ramayah; Mohd Suki, Norazah (Journal of Entrepreneurship, Business and Economics, 2022)
eSports is a novel digital sport that has millions of admirers worldwide.  Researchers have begun looking into eSports player behaviour due to the sport's recent surge in popularity. However, few researchers have studied the factors influencing Malaysians' intention to participate in eSports. This paper reviews the existing literature on user behaviours in participation in eSports to fully understand the elements that affect users' intention to participate in eSports and to serve as a resource for researchers in future research. First, we conducted a literature search using the databases Era, MyCite, Scopus, and SpringerLink, and we found 31 articles that satisfy the requirements. Second, we carried out a descriptive analysis-focused bibliometric evaluation. Finally, to lay a foundation and generate fresh ideas for future study, this work anticipates potential research-based future research topics. Research paper Keywords: eSports; Participation; Behavioural Intention Reference to this paper should be made as follows: Lim, C. N,m Goh, Y. N., Mod Isa, S., Thurasamy, R., & Mohd Suki, N. (2022). A Bibliometric Review on Esports Participation: View from Malaysia. Journal of Entrepreneurship, Business and Economics , 10 (2), 139–171.